Recent advancement and prospective of heterogeneous carbonaceous catalysts in chemical and enzymatic transformation of biodiesel. (1st July 2018) - Dhawane, Sumit H.; Kumar, Tarkeshwar; Halder, Gopinath
Highlights: The methods of carbon material synthesis are illustrated with examples. The successful utilization of carbon materials as catalyst support is discussed. Hydrophobic and well-ordered carbon as support in biodiesel catalysis is reviewed. Analysis of heterogeneous esterification and transesterification is presented. Energy intensive and cost effective green approach for biodiesel synthesis is proposed. Abstract: Carbon derived from waste biomass has emerged as a promising candidate towards the synthesis of catalyst or catalyst support for chemical and enzymatic reactions. Excellent surface properties like large specific surface area and high porosity make carbon an exceptional contender for catalyst support. Moreover, appreciable electron conductivity and relative chemical inertness enrich its applicability in chemical processes. The biomass-derived carbon catalysts are environmentally benign for reducing carbon footprint and cost competitive to other heterogeneous catalysts available for biodiesel production. Carbons functionalized with different alkali metals, SO3 H group, alkoxides, enzymes and transition metals enhance the catalytic activity in the transesterification of triglycerides to alkyl esters. Biodiesel, a promising alternative to the conventional petro-diesel is studied globally in the modern era. The cost-effective process for the biodiesel synthesis involves heterogeneous catalysis employing various catalyst supports. The traditional process of biodiesel synthesis is expensive on the indus trial scale; hence, heterogeneous catalysis plays a vital role in minimizing the cost of the final product due to high stability, efficient activity, and noticeable reusability. For the success of biorefinery concept in the present day and sustainable development towards future, there is a need for the design of a new generation of multifunctional catalysts perhaps consisting of carbon as a support derived from waste biomass. This, in turn, will enhance the selective transformation of non-conventional sources into biodiesel as a sustainable source of energy. Henceforth, the present review offers a broad synopsis on the synthesis of evolving carbonaceous catalysts such as activated carbon, graphene, carbon nanotubes, carbon monoliths and carbon nanohorns for their use in biodiesel production.